The role of changes in indicators of immune response in the formation of structural and clinical manifestations of hypertrophy of lingutical aligment - Andreev, A. V.; Nasibullin, B. A.; Tagunova, I. K. (Journal of Education, Health and Sport, 2017)
The authors based on the results of a comprehensive examination of 32 patients diagnosed with "Hypertrophy of the lingual tonsil", established that the clinical manifestations of this suffering are combined with dystrophic changes in the parameters of the state of the immune response. The latter indicate the development of autoimmune reactions in the body of patients, the activation of humoral mechanisms of regulation of inflammation and the preservation of the activity of the cellular component of the immune response. In this case, the most significant deviations of the studied parameters occurred in patients with the most vivid clinical picture. The authors believe that the disturbance of the immune regulation system is an important pathogenetic factor of the lingual tonsil hypertrophy, which affects the severity of the clinical manifestations of this pathology